Enhancing Reading Skills through Short Stories - Alimova Kamola Mirshahidovna (Researchparks Publishing, 2022)
The article describes the use of short stories in teaching English. Reading occupies an important place in teaching a foreign language. Thanks to it, the teacher can simultaneously solve several educational problems: compensate for the lack of a language environment, fill in gaps in the knowledge of linguistic and cultural material, expand vocabulary, consolidate understanding of grammatical material, etc. And, it is a flexible material that also helps students develop their writing, speaking and listening skills. To do this, it is effective to use specific techniques and post-text exercises: reading for study, reading for speaking, writing, etc.